Presentist Social Functionalism: Bringing Contemporary Evolutionary Biology to the Social Sciences - Schulz, Armin W. (Springer Nature, 2025)
This open access book presents and defends a new approach towards social functionalism: Presentist Social Functionalism. This approach draws on recent developments in evolutionary biology and philosophy of biology to provide a more compelling theoretical foundation for functionalist social analysis. Functionalist approaches to the social sciences—which aim at using facts about what social institutions are for to provide a fulcrum with which to understand, evaluate, and respond to social reality—are about as old as the subject itself, but have also been the subject of much criticism. In particular, a widespread concern for the functionalist tradition in the social sciences is that functional ascriptions often lack a plausible theoretical grounding, and that where such a theoretical grounding can be provided, the empirical presuppositions of this grounding often fail to be met. However, recent developments in evolutionary biology and the philosophy of biology promise to change this situation: they show that functional ascription can be compellingly made in an ahistorical, non-reproduction-based, and non-normative manner, which makes it possible to develop a new account of social functionalism that can fulfil the latter’s theoretical and empirical desiderata. To show this, the book begins by laying out the major existing accounts of social functionalism and detailing their challenges. It then develops the new, alternative account of Presentist Social Functionalism. Given its interdisciplinary nature and application-focused approach, the book is of interest to researchers in a variety of fields, from evolutionary biology to the social sciences and philosophy.